Earliest signs of life on land preserved in ca. 3.5 Ga hot spring deposits - Tara Djokic (Nature Portfolio, 2017)
Some of the earliest life on Earth flourished in terrestrial hot springs. Here, the authors present evidence for ca. 3.5 Ga hot spring deposits from the Dresser Formation, Pilbara Craton, Australia, that host some of the earliest known life in the form of stromatolites and other microbial biosignatures.